2019
DOI: 10.1088/1361-6528/ab2c0d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of 2D Mo2C/graphene heterostructure on liquid Au substrates as enhanced electrocatalytic electrodes

Abstract: 2D Mo2C has drawn considerable interest recently for its excellent properties in 2D superconductivity and enhanced hydrogen evolution reaction (HER). Liquid metals have been demonstrated to be an ideal substrate for large-area 2D Mo2C growth. However, the growth mechanism of 2D Mo2C on liquid metals has rarely been explored. Here we report the synthesis of high-quality 2D Mo2C crystals and Mo2C/graphene heterostructures on liquid Au by chemical vapor deposition method. A sunk growth mode of 2D Mo2C on liquid A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 65 publications
2
46
0
Order By: Relevance
“…Without compromising with growth rate, Mo 2 C films in the nanometer range were achieved even at lower temperatures ∼880 o C 89 . Using the ambient pressure chemical vapor deposition method, another researcher group synthesized 2D Mo 2 C crystals and Mo 2 C/graphene heterostructures on liquid Au surface the temperature above 1100 o C under H 2 90 . The benefits of using Au instead of Cu catalyst is its lower melting point 1064 o C. The surface properties and defect concentration can be engineered through the chemical vapor deposition technique that is the advantage of this method.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Without compromising with growth rate, Mo 2 C films in the nanometer range were achieved even at lower temperatures ∼880 o C 89 . Using the ambient pressure chemical vapor deposition method, another researcher group synthesized 2D Mo 2 C crystals and Mo 2 C/graphene heterostructures on liquid Au surface the temperature above 1100 o C under H 2 90 . The benefits of using Au instead of Cu catalyst is its lower melting point 1064 o C. The surface properties and defect concentration can be engineered through the chemical vapor deposition technique that is the advantage of this method.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…CVD has been a promising technique to achieve large area and high quality thin layers of Mo 2 C 3,13,22,[14][15][16][17][18][19][20][21] . In this method, Cu foil is placed on a Mo substrate and heated.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, Cahitoglu et al 15 used a liquid bimetallic Sn-Cu alloy instead of Cu foil and showed that Mo2C could grow at temperatures as low as 880 °C with sizes of μm in diameter and hundreds of nm in thickness. Sun et al 16 used Au and very recently, Young et al…”
Section: Results Is the Formation Of 2mo + C  Mo2cmentioning
confidence: 99%